The effect of information systems criterion on the EFQM model in institutions of higher education - Ismail, Rosli; Azmi Murad, Masrah Azrifah; A. Jabar, Marzanah; Nor, Rozi Nor Haizan (Science Publications, 2015)
The purpose of this paper is to empirically test the effect of information systems criterion on the European Foundation for Quality Management (EFQM) excellence model in Higher Education Institutions (HEIs). The paper identifies five (5) causal hypotheses from literatures that are related to the information systems criterion. The data were collected from 118 Malaysian higher education institutions through the questionnaire survey. The empirical data were analysed using Structural Equation Model (SEM) via the AMOS version 21 software. The respondents are limited only to the quality managers in Malaysian higher education institutions. The results indicate that there are three (3) significant relations and two (2) insignificant relations within the model. Leadership has positive effects on information systems and information systems have positive effects on policy and strategy; and partnership and resources. However, information systems do not have positive effect on people and processes. By using information systems in EFQM excellence model is necessary for the improvement of quality in the field of higher education institutions.